2018
DOI: 10.7554/elife.27157
|View full text |Cite
|
Sign up to set email alerts
|

The H3K4 methyltransferase Setd1b is essential for hematopoietic stem and progenitor cell homeostasis in mice

Abstract: Hematopoietic stem cells require MLL1, which is one of six Set1/Trithorax-type histone 3 lysine 4 (H3K4) methyltransferases in mammals and clinically the most important leukemia gene. Here, we add to emerging evidence that all six H3K4 methyltransferases play essential roles in the hematopoietic system by showing that conditional mutagenesis of Setd1b in adult mice provoked aberrant homeostasis of hematopoietic stem and progenitor cells (HSPCs). Using both ubiquitous and hematopoietic-specific deletion strateg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 94 publications
1
28
1
Order By: Relevance
“…SETD1B is a maternal effect gene required for the oogenic gene expression program and a novel recurrently mutated gene in chronic myeloid leukemia . SETD1B is essential for hematopoietic stem and progenitor cell homeostasis in adult mice . De novo variants in SETD1B are associated with intellectual disability, epilepsy and autism .…”
Section: Discussionmentioning
confidence: 99%
“…SETD1B is a maternal effect gene required for the oogenic gene expression program and a novel recurrently mutated gene in chronic myeloid leukemia . SETD1B is essential for hematopoietic stem and progenitor cell homeostasis in adult mice . De novo variants in SETD1B are associated with intellectual disability, epilepsy and autism .…”
Section: Discussionmentioning
confidence: 99%
“…In vertebrates, post‐translational modifications of histones, such as methylation, phosphorylation and acetylation, are extensively used to ensure the temporal and spatial expressions of key genes during tissue‐specific differentiation and development . Lysine methylation on histone 3 (H3) is an important part of the epigenetic regulation network and integrates both cooperative and antagonistic modifications .…”
Section: Introductionmentioning
confidence: 99%
“…More recently, detailed analyses have demonstrated the impact of Setd1a and Setd1b deletion on HSPCs during foetal and adult haematopoiesis [ 111 , 112 ]. Vav-Cre-mediated Setd1a loss during foetal development leads to death 7 to 20 days post-birth from a significantly depleted LSK compartment, which must have failed to establish because of Setd1a deficiency in the first definitive HSCs that did not form or expand sufficiently [ 111 ].…”
Section: Setd1a and Setd1b In Haematopoiesismentioning
confidence: 99%
“…Both studies showed that Mll1 does not affect Hoxb4 expression, which may underlie the difference in ESC fate induction. In contrast, to the phenotype for Setd1a deletion, Vav-Cre-specific Setd1b −/− null mice survive to a median of 25 weeks, suggesting that it is dispensable for the specification of a foetal haematopoietic system [ 112 ]. However, Setd1b −/− null foetal HSPCs were not tested in any functional assays.…”
Section: Setd1a and Setd1b In Haematopoiesismentioning
confidence: 99%
See 1 more Smart Citation